The diagnostic and therapeutic evaluation of Idiopathic granulomatous mastitis. A case series - Barman, Amalesh; Barman , Ayanti; Khan , Miraj Ali; Ranajit Bari (Asian Journal of Medical Sciences, 2023)
Idiopathic granulomatous mastitis (IGM) is a rare chronic inflammatory condition of the breast that is commonly found in young women of childbearing age with a history of recent breastfeeding. In our study, we aimed to present the detailed clinical and morphological features of IGM cases, diagnostic clues, and treatment. The most common clinical presentation is a unilateral, breast induration, nipple retraction, and even a multiple sinus formation often associated with an inflammation of the overlying skin. It usually mimics with breast abscess, rarely inflammatory breast cancer. Although etiology is still unknown. Many factors, including autoimmunity, infection, chemical agent, lactation, and hormonal imbalance, are supposed to play a role for etiology. Therefore, thorough history taking, examination, imaging, and histopathology make a proper diagnosis that determines the optimal management to be administered. We are presenting three cases of granulomatous mastitis from our clinical practice with varying clinical features. After the necessary investigation, we diagnose it as IGM. There is no definitive treatment guideline still now. In literature, many therapeutic operations, including conservative treatment, surgery, steroid, and immunotherapy, have been shown. However, we successfully treated this patient by conservative treatment, by incision and drainage, surgical debridement, or by in a combination of both, followed by regular dressing, antibiotics, and other supportive measures with no use of the steroid.